The Anguren account of the Balangiga incident, its context and aftermath - Rosaldo, Eustaquio B.; Borrinaga, Rolando O. (2007)
This paper presents, annotates, and contextualizes a previously unknown eyewitness account of a leading participant of the ?Balangiga Massacre,? the famous Filipino attack on Company C, Ninth U.S. Infantry Regiment, in Balangiga, Eastern Samar, on September 28, 1901. The Anguren Account provides enriching details about the revolutionary situation in southern Samar before and after the arrival of the Americans in Balangiga town, the preparation for the attack on Company C, the attack itself, and the subsequent reprisal of the U.S. military on Quinapondan, which was served by the parish priest of the adjacent town of Balangiga.